NEW APPROACH IN DESIGN OF EDUCATION RESOURCES FOR THE MANAGERS IN NANOINDUSTRY - Tatyana A. Gavrilova; Margarita A. Gladkova (Открытое образование (Москва), 2016)
The article deals withe the problems of designing education resources for the future managers in the fi eld of high and nano-tech. Modern high-tech companies are in need of highly qualifi ed managers who are capable of managing innovation projects and commercialize them. At present there exist extra curricular programmes whereas there are no special higher education programmes for specialists of this level. Authors of the article offer a new system approach to design education resources based on such a programme. It is based on the usage of instruments of the modern smart-cards for presenting the structure of education resources. This kind of presentation enables to form the content of education resources clearly and vividly at different levels simultaneously as well as determine the elements which either are in demand, or intersect, or are superfluous.